Collaborative Guided Inquiry for Chemistry Learning Outcomes Improvement on Solubility Product Concept - Nugraheni, Putranty Widha (Program Studi Pendidikan IPA, FKIP Universitas Pancasakti (UPS) Tegal, 2022)
This research aims to know the implementation of the learning model and the effect of the performance of the guided inquiry collaborative learning model on the students' achievement on solubility and solubility product concepts. This study used the design of experiments and was conducted in 11th grade at Malang High School in the group's pretest and post-test design. Data were collected using a multiple-choice test and analyzed using descriptive and inferential statistics (t-test). Student worksheets and proficiency tests in solubility and solubility product concepts were classified as valid and very effective. In addition, each learning phase of the timetable was adequately implemented. The study showed an effect of implementing the guided inquiry cooperative learning model on the students' achievement on solubility and solubility product. The student's cognitive achievements taught by collaborative guided inquiry had higher achievement (the average score was 80.83) than those led by guided inquiry (the average score was 70.93).